The Influence of PAI Learning Outcomes and Learning Motivation on Students’ Honesty Character - Alkhairi, Aulia Azmi; Nida, Sofwatun; Dewanti, Sintha Sih (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2024)
The objectives of this study are to (1) identify the impact of PAI learning outcomes on student characteristics, (2) identify the influence of learning motivation on student characteristics, and (3) identify the combined influence of learning motivation and PAI learning outcomes on student characteristics. The sample for this study involves 60 high school students in Yogyakarta. Data was collected using a questionnaire as the instrument. The classical assumptions applied include normality, multicollinearity, heteroscedasticity, and homogeneity. The hypothesis assumptions used include the t-test, coefficient of determination (adjusted R2), F-test, and multiple linear regression. Based on the research results, (i) PAI learning outcomes did not show a significant difference in students’ honesty characteristics with a value of 0.900; (ii) learning motivation showed a significant difference in students’ honesty characteristics with a value of 0.000; and (iii) PAI learning outcomes and learning motivation showed an influence both exclusively and simultaneously with a value of 0.000. Based on these findings, it can be concluded that students’ learning outcomes and motivation affect the characteristics of students’ failure in PAI classes at high schools in Yogyakarta. This study is expected to facilitate all parties in evaluating PAI learning outcomes and gradually increasing learning motivation, in order to improve students’ performance characteristics and advance research in the future.